Modifikasi Proses Pengolahan Kopi Arabika Menggunakan Metode Honey Process - Hazfri Dalimunthe; Dina Mardhatilah; Maria Ulfah (The University of Lampung, 2021)
The amount of mucilage can be adjusted according to the washing intensity. The level of ripeness of the coffee fruit is also directly proportional to the mucilage constituent components. Optimally ripe coffee cherries have a higher sugar, protein, lipid and water content than raw coffee cherries. So that research is needed to determine the effect of washing intensity and level of ripeness of coffee cherries on the characteristics of the resulting taste of coffee. The research design used was a complete two-factor block design. The first factor is the intensity of washing mucilage that sticks to the surface of the coffee beans; 2 times washing, 1 time washing, without washing. The second factor is the level of ripeness of the coffee cherries; raw coffee cherries, optimally ripe coffee cherries, past ripe coffee cherries. The analyzes were carried out, namely water content, ash content, total sugar content, pH value, Brix, and organoleptic test using the SCAA cupping method. The results of this study indicate that washing intensity affects the Brix value, water content, total sugar content, and pH. Whereas in the second factor, the level of ripeness of the coffee fruit affects the Brik value, water content, total sugar content, and pH. This study also showed that there was a correlation between washing intensity and the level of ripeness of the coffee cherries and the preference of the panelists. The non-washing treatment (black honey) and the optimal level of ripeness were the most preferred by the panelists, all coffees produced from this study met SNI 01-3542-2004. Keywords: arabica characteristics, honey process, maturity level, washing intensity